The Application of Apostille to Document Validation and Its Impact on the Role of Notaries in Indonesia from an International Legal Perspective - Amalia, Dwi Nadrita; Sri Darmadi, Nanang; Handoko, Widhi (TABELLIUS: Journal of Law, 2026)
This study aims to analyze: 1) PThe implementation of the Apostille process in Indonesia and the perspective of international law. 2) The implementation of the Apostille system affects the role and responsibilities of notaries in Indonesia. This type of research is normative legal research. The type of data in this study is secondary data. The data collection method uses observation, interviews, and library techniques (document study). The analysis in this study is qualitative. The results of the study concluded: 1) The implementation of Apostille replaces layered legalization with an efficient and internationally recognized public document validation mechanism. The 1961 Hague Convention simplifies document proof through a single official certificate, while in Indonesia the legal basis is stated in Presidential Regulation No. 2 of 2021, Permenkumham No. 6 of 2022, and Decree of the Minister of Law and Human Rights No. M.HH-01.AH.03.01 of 2022, with the Ministry of Law and Human Rights as the Competent Authority through the apostille.ahu.go.id portal, creating efficiency, transparency, and legal certainty. 2) The implementation of the Apostille expands the role of notaries from merely national deed-making officials to legal actors in the international civil evidence system. Notaries are now responsible for ensuring that each deed meets the formal requirements of Article 38 of the UUJN, the validity of the signature and official stamp, and the conformity of the data with the specimen signature in the Ministry of Law and Human Rights database so that the document can be affixed with an Apostille Certificate. In addition to formal responsibilities, administrative aspects require precision in document verification and electronic legalization procedures (Cyber Notary), while ethical responsibilities require integrity, intellectual honesty, and caution to avoid harm to others. In the digital era, notary responsibilities also include cybersecurity and personal data protection in accordance with Law No. 27 of 2022, so that electronic deeds remain valid, authentic, and trusted internationally. Thus, the Apostille system strengthens the strategic position of notaries as guardians of the credibility of Indonesian law, demanding professionalism, accountability, and mastery of digital legal technology.